Teoria del placebo in medicina e psicologia versus teoria della suggestione in psicanalisi: una valutazione epistemologica - Cagna, Pamela (Metapsychologica - rivista di psicanalisi freudiana, 2023)
Two theoretical models are here compared: the theory of placebo in medicine and psychology, and the theory of suggestion in psychoanalysis. Their strengths and weaknesses are pointed out, particularly in relation to the issue of empirical objectivity in the natural sciences. Current discussions on the problem of placebo entirely overlook the longstanding and fascinating debate on the problem of suggestion, which took place between the second half of the 1800s and the first half of the 1900s. Specifically, they disregard one insightful observation that Freud made as early as in 1888: that suggestion features both an objective aspect, which lies in that many physiological phenomena have a psychological correlate, as well as a subjective aspect, which is the influence the therapist exerts on the patient, consciously or unconsciously. Allowing for the distinction between these two components within the model enables psychoanalysts to solve the methodological problem of warranting the objectivity of their theories, and it can also trace the path to further development for medicine and psychology.